A Historical-Institutionalist Framework for Analysing Copyright Policymaking - Haggart, Blayne (Copyfight, 2014)
Copyright law is the outcome of historically contingent processes and cannot be understood outside of the political forces that shape it. Because copyright is perpetuated by the exercise of power, understanding the power relations of copyright – who makes the rules, how they do so, and who wins and loses – is essential to our understanding of what IP is, how it is perpetuated, and even if it is necessary. Providing a complete picture of the linkages among copyright-reform efforts in three countries is complicated by the fact that a countryʹs copyright law is embedded within domestic political institutions, regional